Implementasi Prinsip Utmost Good Faith oleh Perusahaan Asuransi dalam Masa PKPU Terhadap Hak Pemegang Polis - Putri, Gracia; Lie, Gunardi (Universitas Ekasakti, 2023)
The existence of insurance in human life can provide a sense of security because in carrying out its duty, it is carried out in accordance with the principle of utmost good faith. However, the principle of utmost good faith cannot always be perfectly implemented. There are many factors that influence the implementation of the principle of utmost good faith in the world of insurance. One of them is related to the implementation of the principle of good faith by insurance companies during the suspension of payment (PKPU) period regarding the rights of policy holders. This research was carried out in a normative juridical manner using library approach techniques. The research results show that there is a polemic regarding the scope and time limits for applying the principle of utmost good faith as well as the position of policy holders in filing PKPU lawsuits. Thus, it is still necessary to evaluate the applicable laws and regulations and to provide legality to policy holders so that the rights and obligations of the parties can be carried out even though the insurance company is in the PKPU period.